TINDAK TUTUR DIREKTIF ORANGTUA TERHADAP ANAK DALAM BAHASA MELAYU DIALEK KUANSING - Sari, Yesi Kamala; Burhanudin, Dudung; Hermandra, Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the form and function of parents' directive speech acts against children in the Malay language of Kuansing dialect. This research is a qualitative research description. The subjects in this study were 10 members of the H. Selamet extended family of hamlet III Pebaun Hulu Village, Kuantan Mudik District, Kuantan Singingi Regency. The instrument used in this study was to search for, obtain and obtain own data, namely by interviewing, chatting or discussion, and equipped with supporting tools such as recording equipment, and small notebooks. The results of the study have been carried out as a whole of 10 family subjects, there are 2 forms of directive speech acts and 22 directive speech acts functions and each of the forms and functions has been described. The form of directive speech acts consists of 10 data while the directive speech acts function is obtained 101 data suggest. Key Words: Directive Speech Acts, Parent And Child Interactions